Effect of Liquid Organic Fertilizer and Cuttings of Bulbs on Growth and Production of Shallots (Alium Ascalonicum L.) - Aris Safrudin; Abdul Wachid (Nabatia, 2015)
The aim of this study was to determine the effect of the concentration of liquid organic fertilizer and seed tuber cutting against to growth and production of onion. Experiment was arranged in a factorial experiment using a randomized block design (RBD) and repeated 3 times. Factorial I was concentrationof liquid fertilizer comprises four levels: 0,2.4, and 6 cc/liter of water; factor II was piece of tuber shoots comprises 3 levels: no cutting, cutting 1/4 and ½ part cutting the tubers sprout. The measured variables were plant length, number of leaves, number of tillers, root length, weight stover, fresh weight and dry weight of tubers. Data were analyzed by ANOVA followed by a test ynag HSD 5%. The results showed concentration of organic fertilizer influence on the plant long parameter age of 14, 21 and 28 days after planting, and the number of leaves at the age of 14 and 21. Cutting seed tubers affect the number of leaves aged 14, 21 and 28 days after planting. There is an interaction effect between kosnetrasi organic liquid fertilizer by cutting the tubers lip on the length of the plant ages 35, 42 and 49 days after planting, the number of leaves of the plant ages 28, 35, 42 and 49 days after planting, and the panang roots, weights stover, fresh weight and dry weight of tubers red onion. Combination treatment liquid fertilizer concentrations of 6 cc/liter and ½ part cutting buds bulbs given the best results.